Instability of solutions for certain nonlinear vector differential equations of fourth order - Tunç, C. (Нелінійні коливання, 2009)
The main purpose of this paper is to give a result with an explanatory example which deals directly with
the instability of the trivial solution of a certain nonlinear vector differential equation of fourth order. The
result which will be established here improves and includes a well-known instability result in the literature
established for a scalar nonlinear differential equation of fourth order. Отримано результат iз пояснювальним прикладом про нестiйкiсть тривiального розв’язку деякого нелiнiйного векторного диференцiального рiвняння четвертого порядку, що покращує
вiдомий результат про нестiйкiсть для скалярного диференцiального рiвняння четвертого порядку.